ØªØ·ÙˆÙŠØ± Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø§Ù„Ù…ØØªÙˆÙ‰ Ø§Ù„Ù…ØÙ„ÙŠ (Muatan Lokal) ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØºÙŠØ± Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ù‡Ø§ ÙÙŠ Ù„ÙˆÙ…Ø¨ÙˆÙƒ Ø§Ù„Ø´Ø±Ù‚ÙŠØ© - Baiq Sugestina; Dony Handriawaan (Lughatu Ad-Dhat, 2022)
This article tries to find the best solution of the low reading interest of Arabic texts of students (non-native speakers) at MTs Raudhatul Azhar Masbagik Timur, which has an impact on students' ability to read Arabic texts. One of the mainly problems is that teaching materials are less relevant to the local context. Therefore, this study aims to develop a local content-based learning model that is adapted to the existing learning materials in schools. Learning materials with the theme of local content will be able to grow-up students' interest in reading Arabic texts because what is presented in the form of regional uniqueness and potential. By using the research and development method of Bord and Gall model, based on the development needs that researchers carried out, this stage was simplified into 7 stages, namely: Potential and Problems, Information Gathering, Product Design, Design Validation, Design Improvement, Product Trial, and Product Revision. The results of this research are in the form of teaching materials â€œBacaan bahasa Arab berbasis muatan lokal untuk Madrasah Tsanawiyah kelas IXâ€ has been validated by 2 experts, namely material experts and design experts (media). After validation, the next stage was revision based on suggestions from experts, then tested on 34 students at MTs Raudhatul Azhar Masbagik Timur with a student satisfaction test result of 83,8%. From the datas, the average pre-test is 47,79 and the post-test is 60,59. It shows that post-test biggest than pre-test. It means that there is a difference in the average student learning before and after treatment. And this study shows that the use of a local content-based learning model can improve the Arabic reading ability of class IX students of MTs Raudhatul Azhar Masbagik Timur in the 2021/2022 AD academic year.